A Closer Look at the Validity and Reliability of the Persian Versions of National Institute of Health Stroke Scale and Modified National Institute of Health Stroke Scale in Hospitalized Patients: - Amir Behghadami, Mehrdad; Janati, Ali (Galen Medical Journal, 2019)
Â  Â 